Quinolone Resistance: Much More than Predicted - Hernandez, Alvaro; Sanchez, Maria B.; Martinez, Jose L. (Frontiers in Microbiology, 2011)
Since quinolones are synthetic antibiotics, it was predicted that mutations in target genes would be the only mechanism through which resistance could be acquired, because there will not be quinolone resistance genes in nature. Contrary to this prediction, a variety of elements ranging from efflux pumps, target-protecting proteins and even quinolone-modifying enzymes have been shown to contribute to quinolone resistance. The finding of some of these elements in plasmids indicates that quinolone resistance can be transferable. As a result, there has been a developing interest on the reservoirs for quinolone resistance genes and on the potential risks associated with the use of these antibiotics in non-clinical environments. As a matter of fact, plasmid-encoded, quinolone-resistance qnr genes originated in the chromosome of aquatic bacteria, thus the use of quinolones in fish farming might constitute a risk for the emergence of resistance. Failure to predict the development of quinolone resistance reinforces the need of taking into consideration the wide plasticity of biological systems for future predictions. This plasticity allows pathogens to deal with toxic compounds, including those with a synthetic origin as quinolones.